Immunomodulatory effects of the Bifidobacterium longum BL-10 on lipopolysaccharide-induced intestinal mucosal immune injury - Dong, Jiahuan; Ping, Lijun; Cao, Ting; Sun, Lenan; Liu, Deyu; Wang, Song; Huo, Guicheng; Li, Bailiang (Frontiers in Immunology, 2022)
The intestine is the largest digestive and immune organ in the human body, with an intact intestinal mucosal barrier. Bifidobacterium longum is the specific gut commensals colonized in the human gut for boosting intestinal immunity to defend against intestinal mucosal immune injury. In the LPS-induced intestinal injury model, the Bifidobacterium longum BL-10 was suggested to boost the intestinal immune. Detailly, compared with the LPS-induced mice, the BL10 group significantly reduced intestine (jejunum, ileum, and colon) tissue injury, pro-inflammatory cytokines (TNF-α, IFN-γ, IL-2, IL-6, IL-17, IL-22, and IL-12) levels and myeloperoxidase activities. Moreover, the B. longum BL-10 significantly increased the number of immunocytes (CD4+ T cells, IgA plasma cells) and the expression of tight junction protein (Claudin1 and Occludin). B. longum BL-10 regulated the body’s immune function by regulating the Th1/Th2 and Th17/Treg balance, which showed a greater impact on the Th1/Th2 balance. Moreover, the results also showed that B. longum BL-10 significantly down-regulated the intestinal protein expression of TLR4, p-IκB, and NF-κB p65. The B. longum BL-10 increased the relative abundance of the genera, including Lachnospiraceae_NK4A136_group and Clostridia_UCG-014, which were related to declining the levels of intestinal injury. Overall, these results indicated that the B. longum BL-10 had great functionality in reducing LPS-induced intestinal mucosal immune injury.